Sistem Rekomendasi Pekerjaan di bidang IT Menggunakan Algoritma Content-Based Filtering - Crismastiana Koloman; Raihan Maulana; Raisya Dwi Zahra Putri; Wahyu Abadi Harahap (Journal of Creative Student Research, 2023)
Rapid growth in the Information Technology (IT) industry has created an abundance of career opportunities, but job seekers often face difficulty in finding jobs that match their background and skills. To overcome this challenge, this research presents a “Job Recommendation System” that focuses on the IT industry. The method used in this research is "Content-Based Filtering," which allows the system to recommend jobs based on similarities between the skills possessed by the user and the available job descriptions. The system allows users to enter their skills, and based on these skills, analyzes the description jobs to recommend suitable jobs. Apart from providing job recommendations, this method also helps users to identify skill areas that need improvement. The research results show that the content-based filtering method is a powerful approach for providing relevant and effective job recommendations in the IT industry. This method provides great benefits to job seekers, helping them find job opportunities that suit their background and skills. In addition, this method has the potential to be applied in various applications in various industries.